Entrepreneur’s Adaptability Mindset and Its Impact on Business Sustainability - Waware, Vaishali (Digital Repository of Theses, 2024)
Entrepreneurs' adaptability refers to the capability of business owners to recognize and respond effectively to changes, thereby enhancing their organization's resilience and performance. Understanding the relationship between entrepreneurs' adaptability and business growth is essential for academic research and practical implications, particularly in emerging economies like India. The high failure rate among small and medium-sized enterprises (SMEs) in India poses a significant threat to the country's long-term and sustainable development (Singh, 2020). As indicated by Bansal (2010) In the fast-changing world of entrepreneurship, adaptability is not just a desirable trait, it's a survival imperative. The study explores the entrepreneur's adaptability mindset and its impact on business sustainability to raise awareness among entrepreneurs to accept adaptability as a vital business skill and strategize to navigate their businesses accordingly. Research methods include qualitative data from a sample population of twenty-five small and medium-scale entrepreneurs from different states of India. Purposive sampling was applied using semi-structured in-depth telephonic interviews. The data were analyzed using inductive coding of phrases and the frequency of words and phrases were searched to create a thematic analysis. The triangulation approach was used to cross-validate the study. The result shows a positive and strong correlation between entrepreneurs' adaptability mindset and its impact on business sustainability. The factors considered encompass organizational culture, personnel development, technological flexibility, and the comparative alignment of conservative and non-conservative approaches for entrepreneurs' flexibility and businesses' sustainability. The research has revealed a strong correlation between the “Entrepreneur's Adaptability” and “Business Sustainability” variables. The study can be useful to micro, small, and medium-scale businesses as it can raise awareness about the significance and implications of the research. The research can make a significant contribution to knowledge and business practices by addressing key gaps and fragmented understanding in the existing literature by synthesizing insights from diverse scholarly works and offering a comprehensive framework for understanding adaptability in entrepreneurship. The research findings have important implications for business practices and policies, offering management and organizational leaders actionable insights. The limitation of the study is its dependency on self-reported data, which may introduce biases and inaccuracies, focus on explicitly Indian geographical context, which can limit the generalizability of findings to other cultural or economic conditions, and overlooking certain contextual factors such as industry dynamics, firm size, or the regulatory environment. Future research is required to carry out a relative identification explaining how the organization culture, automation, hybrid work culture, retention of the young tech-savvy workforce, and development of teams influence the entire organizational ecosystem considering industry type, size, and region.